PENGARUH RETURN ON ASSETS (ROA) DAN RETURN ON EQUITY (ROE) TERHADAP EARNING PER SHARE (EPS) PADA PERUSAHAAN ASURANSI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rafika - Diaz; - - Jufrizen (JURNAL ILMIAH MANAJEMEN & BISNIS, 2014)
This study aims to determine the effect of Return On Assets (ROA) of theEarning Per Share (EPS), the influence of Return On Equity (ROE) to EarningPer Share (EPS) and to determine the effect of Return On Assets (ROA) andReturn on Equity (ROE) to Earning Per Share (EPS) on insurance companieslisted on the Indonesia Stock Exchange. The results of this study indicate that theReturn On Assets partially do not have significant effect on Earning Per Share.Same thing with Return On Equity is partially no significant effect on Earning PerShare. However, Return on Assets and Return on Equity simultaneous significanteffect on Earning Per Share.